Microenvironmental modulation in tandem with human stem cell transplantation enhances functional recovery after chronic complete spinal cord injury. (April 2023) - Hashimoto, Shogo; Nagoshi, Narihito; Shinozaki, Munehisa; Nakanishi, Katsuyuki; Suematsu, Yu; Shibata, Takahiro; Kawai, Momotaro; Kitagawa, Takahiro; Ago, Kentaro; Kamata, Yasuhiro; Yasutake, Kaori; Koya, Ikuko; et al.
Abstract: While rapid advancements in regenerative medicine strategies for spinal cord injury (SCI) have been made, most research in this field has focused on the early stages of incomplete injury. However, the majority of patients experience chronic severe injury; therefore, treatments for these situations are fundamentally important. Here, we hypothesized that environmental modulation via a clinically relevant hepatocyte growth factor (HGF)-releasing scaffold and human iPS cell-derived neural stem/progenitor cells (hNS/PCs) transplantation contributes to functional recovery after chronic complete transection SCI. Effective release of HGF from a collagen scaffold induced progressive axonal elongation and increased grafted cell viability by activating microglia/macrophages and meningeal cells, inhibiting inflammation, reducing scar formation, and enhancing vascularization. Furthermore, hNS/PCs transplantation enhanced endogenous neuronal regrowth, the extension of graft axons, and the formation of circuits around the lesion and lumbar enlargement between host and graft neurons, resulting in the restoration of locomotor and urinary function. This study presents an effective therapeutic strategy for severe chronic SCI and provides evidence for the feasibility of regenerative medicine strategies using clinically relevant materials.